Electoral Reforms for a New India: Democracy at 100 Years of Independence - Chanabasappa Gunadal (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
India’s journey through a century of independence has been deeply intertwined with the evolution of its democratic institutions and electoral mechanisms. Despite being the world’s largest democracy, persistent structural, legal, and institutional challenges continue to undermine the integrity, inclusiveness, and credibility of India’s electoral system. This paper examines the critical need for electoral reforms in the contemporary era, especially in the context of India’s centenary of independence. Drawing on secondary sources, constitutional provisions, judicial pronouncements, and reports by commissions, this qualitative study outlines the major bottlenecks in India’s electoral democracy, evaluates past reform efforts, and proposes a roadmap for future change. Key findings suggest that strengthening institutional autonomy, enhancing transparency in political funding, synchronizing elections, adopting advanced technology prudently, and reforming internal party democracy are vital. The limitations of this study stem from its reliance on secondary literature and lack of primary field data. Nevertheless, the paper offers a coherent set of recommendations to revitalize Indian democracy in its second century.